HUBUNGAN MANAJEMEN HUMAS DENGAN PEMBANGUNAN CITRA SEKOLAH DI SMP IT TUNAS CENDEKIA MATARAM - Made Piliani; Anak Agung Rai Sunanjaya (Jurnal Paedagogy, 2016)
The purpose of this study was to determine the relationship between public relations management and image building of schools in SMP IT Tunas Cendekia Mataram. To obtain research data, the data collection technique used was the questionnaire method as the main method and observation and documentation as a complementary method. Furthermore, the data analysis method uses statistical analysis methods with the product moment correlation formula. Based on the results of data analysis in this study, the r count value was 0.866 and then this value was consulted with the product moment r table value at the 5% significance level with N = 66 obtained a value of 0.254. This fact shows that rcount is greater than rtabel or 0.866> 0.254, then the results of data analysis in this study are declared "significant", that is, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Thus it can be concluded that "There is a Relationship between Public Relations Management and School Image Development at SMP IT Tuas Cendekia Mataram which is included in the" strong "category.